Peningkatan Pemahaman Story-Driven Marketing pada Legenda Batu Parsidangan Huta Siallagan Samosir, Sumatera Utara - Posma Sariguna Johnson Kennedy (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Marketing techniques using storytelling are considered to have the opportunity to increase the number of tourist visits. This activity explores storytelling in the Huta Siallagan tourism object, Samosir Regency, North Sumatra. This tourist attraction has the opportunity to be developed because it has historical value and uniqueness, and folklore. This activity was carried out using discussions with Chairman Huta Siallagan to gain an increased understanding of how the legend of the parsidangan stone became a tourist attraction that functions as a criminal court. The implementation was carried out directly at the Huta Siallagan Tourism Object. The writing method used is a qualitative method, which can explore and understand the meaning of social or humanitarian problems. King Siallagan's Stone Chair is a historical relic and archaeological objects in the form of stone chairs and tables. The stones are believed to be more than 200 years old, revealing a cruel practice in Samosir in the past, namely the story of the cannibalism of the Batak Tribe. With long discussions and interviews, we can understand the importance of storytelling in increasing the number of visitors to tourism objects, especially in Huta Siallagan.